Plant Species Composition and Community Perception Towards Landscaping Work Executed at Hawassa University-Main Campus, Ethiopia - Birhanu Kagnew; Firew Kebede (East African Journal of Biophysical and Computational Sciences)
Landscaping is making visual improvements to academic institutions, urban and other private organizations with plants and attractive materials. People all over the world are attracted to green and beautiful landscapes which initiate them to be happy and creative. Especially students in higher educational institutions who spend much of their time focused on their studies need of clean, green and attractively well-designed landscape in their campus. So far data on plant species composition and perception of university towards landscape work is lacking. With this understanding, the study was conducted to investigate plant species composition and community perception towards landscaping work executed at Hawassa University’s main campus using questionnaires, interviews, observation and group discussion methods. In addition, vegetation data were collected using systematic sampling method. In the study, 221 respondents were drawn from academic staff, administrative workers and students using random sampling method. Key informants were selected using purposive sampling method. In order to identify the plant species, systematic sampling along the transect line was employed. Twelve (12), 40m X 40 m  (i.e. 1600 m2) area quadrat plots were laid and all the plants species in the quadrats were collected and identified. The distance between each transects and quadrat was 200 m and 100m, respectively. 52 plant species with 44 genera and 29 families were recorded. The study showed that, the most dominant family was Fabaceae with 9 species followed by Cupressaceae as well as Moraceae with 4 species each respectively. The results revealed that, campus landscaping work was the most significantly important and made the campus more attractive by plantation (61.1%), landscaping (27.1%) and walkways (5.7%). Plantation could also modify the micro-climate of the campus environment (94.3%) due to the plants photosynthesis process which produces O2 and takes in Co2 from the atmosphere. In general educational institutions landscaping need to be encouraged to enhance the teaching-learning process, and to make the working environment attractive. A great educational environment is guided by the most powerful teacher of all, nature itself